Enhancing interpreting performance, engagement, and self-regulated learning through peer assessment: an attachment theory perspective - Yang, Chunwen; Hou, Shuai; Chen, Jing (Frontiers in Psychology, 2025)
This study addresses the challenge of limited personalized feedback in interpreter training, which often hinders students’ engagement, self-regulation, and performance development. Guided by Attachment Theory, it explores how peer assessment can serve as a secure relational scaffold that enhances learning outcomes. Employing a quasi-experimental design with 30 undergraduate interpreting students divided into experimental and control groups, the study combined pre- and post-tests with surveys and thematic analysis to evaluate interpreting performance, engagement, and self-regulated learning (SRL). Quantitative results showed significant improvement in interpreting performance, engagement, and SRL in the peer-assessment group, while qualitative findings revealed improved confidence, reflective thinking, goal-setting, and peer support. Peer assessment fostered emotional safety, motivation, and strategic learning behaviors that enhanced both engagement and SRL. These findings imply that attachment-informed peer feedback can strengthen interpreters’ cognitive, affective, and behavioral learning dimensions, promoting sustainable skill development and learner autonomy. Overall, the study underscores the pedagogical value of designing peer assessment practices that balance evaluative rigor with psychological safety in interpreter training.